The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/016146811912100702
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant-Origin Students in Community College: How Do They Use Their Time on Campus?

Abstract: Background Immigrant-origin students are the fastest growing new population in community colleges, making up nearly a third of the community college population. To date, little is known about how immigrant-origin students make use of their time on community college campuses. Purpose This study sought to understand in what ways and to what extent immigrant-origin students—defined as first-generation (foreign-born) or second-generation (born in the United States to immigrant parents)—used their out-of-class camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Additionally, Lewis et al (2021) found that African American students at a PWI experienced particularly high rates of racism, which negatively impacted their sense of belonging. Similarly, for other minoritized students, researchers have found that marginalization and hostile campus climates affect students’ belongingness, academic achievement, and well-being (Burgos-Cienfuegos et al, 2015; Hernandez et al, 2019; Hurtado & Carter, 1997; Stephens et al, 2012). Greater college belongingness also correlates positively with life satisfaction for first-generation college students (Duffy et al, 2020) and negatively with anxiety and depression, with stronger associations for first-generation and racially/ethnically minoritized students (Gopalan et al, 2022).…”
Section: College Belongingmentioning
confidence: 99%
“…Additionally, Lewis et al (2021) found that African American students at a PWI experienced particularly high rates of racism, which negatively impacted their sense of belonging. Similarly, for other minoritized students, researchers have found that marginalization and hostile campus climates affect students’ belongingness, academic achievement, and well-being (Burgos-Cienfuegos et al, 2015; Hernandez et al, 2019; Hurtado & Carter, 1997; Stephens et al, 2012). Greater college belongingness also correlates positively with life satisfaction for first-generation college students (Duffy et al, 2020) and negatively with anxiety and depression, with stronger associations for first-generation and racially/ethnically minoritized students (Gopalan et al, 2022).…”
Section: College Belongingmentioning
confidence: 99%